Peran Pendidikan Pancasila sebagai Pembentuk Karakter Mahasiswa - Hayqal, Muhammad Raya; Najicha , Fatma Ulfatun (Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2023)
The Role of Pancasila Education as a Student Character Builder. This article was prepared to find out whether there is a role of Pancasila education in the formation of student character. Pancasila education in higher education can be expected as the spearhead of character building for students so that students can practice the precepts contained in Pancasila well in their daily lives. Because the precepts contained in Pancasila are the basic values of the state that are intact so that the basis of the state can have an important meaning for the Indonesian nation and closely related to Indonesian society. The research method used is a literature study, where researchers read and search for information through books, journals, and other literature sources relevant to the topic discussed. The results of this study indicate that the role of Pancasila education at the tertiary level has an important impact on improving student character, because Pancasila has an important and major influence on efforts to develop intelligence, imagination, character and noble character if Pancasila is practiced in everyday life properly and correctly